1999
DOI: 10.1002/(sici)1521-4109(199906)11:8<541::aid-elan541>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Channel Microband Electrode Arrays for Mechanistic Electrochemistry. Two-Dimensional Voltammetry: Electrode Kinetics

Abstract: The theory of``two-dimensional voltammetry'' using arrays of gold channel microband electrodes ranging in size from the millimeter to the micrometer scale is extended to permit the deduction of electrochemical rate constants through the analysis of hydrodynamic voltammograms as a function of both electrode size and electrolyte¯ow rate (convection). The technique is applied to the reduction of p-chloranil and the oxidation of 2,3,7,8-tetramethoxythianthrene both in acetonitrile solution and electrochemical rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Microband electrodes are of interest to electrochemists for their ease of fabrication to specific measurements [4,5], and application within channel systems [6][7][8][9][10][11][12][13]. Utilising an array of band electrodes, of alternate 'generator-collector-generator' modes utilising anodic and cathodic potentials, allows the 'redox cycling' of target analytes by measuring diffusion from the generator microbands to the collector microbands [14][15][16][17][18][19].…”
Section: Microband Electrodessupporting
confidence: 55%
“…Microband electrodes are of interest to electrochemists for their ease of fabrication to specific measurements [4,5], and application within channel systems [6][7][8][9][10][11][12][13]. Utilising an array of band electrodes, of alternate 'generator-collector-generator' modes utilising anodic and cathodic potentials, allows the 'redox cycling' of target analytes by measuring diffusion from the generator microbands to the collector microbands [14][15][16][17][18][19].…”
Section: Microband Electrodessupporting
confidence: 55%
“…(11). Application of this equation gave a physically reasonable value of D of 1.43 · 10 À5 cm 2 s À1 , compared to 1.75 · 10 À5 and 1.87 · 10 À5 cm 2 s À1 reported by Compton et al [25,26] in this solvent. This implies that the diffusion fields to the individual pores overlap so that the total geometric surface area of the underlying electrode becomes active, even though only a small fraction of the electrode is exposed.…”
Section: Voltammetry Of Pet Membranes With Micron Scale Poressupporting
confidence: 70%
“…10 À2 cm s À1 . We note that Prieto et al [26] have reported a k 0 value of 0.062 cm s À1 for p-chloranil reduction at gold electrodes in acetonitrile solution.…”
Section: Voltammetry Of Pet Membranes With Micron Scale Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…The channel flow electrode is widely used in electrochemistry in a number of applications [1][2][3][4][5][6][7], most notably for the reliable measurement of the fastest, outer sphere electrochemical rate constants and the validation of Marcus theory [8][9][10][11]. Its hydrodynamic nature results in larger and more reproducible current responses, while the well-defined parabolic flow pattern makes it an ideal candidate for rigorous theoretical modelling [12].…”
Section: Introductionmentioning
confidence: 99%